VÍNCULO MÃE-FILHO E OPORTUNIDADES PARA O DESENVOLVIMENTO MOTOR DE LACTENTES EXPOSTOS E NÃO EXPOSTOS AO HIV (Movimenta (ISSN 1984-4298), 2022)
Aim: To characterize and evaluate the mother-child bond, home opportunities and motor development of infants exposed and non-exposed to HIV between 4 to 12 months of age. Methods: Cross-sectional study with 48 infants and their mothers, 21 exposed to HIV and 27 non-exposed to HIV. Mothers responded to the Mother-Child Bond Assessment Protocol, the Affordances in the Home Environment questionnaire, motor development was assessed by the Alberta Infant Motor Scale (AIMS). Pearson’s correlation was applied, and significance level p-value
Keywords: Vertical Infectious Disease Transmission